2020
DOI: 10.1590/1678-992x-2019-0025
|View full text |Cite
|
Sign up to set email alerts
|

Early defoliation effects on water status, fruit yield and must quality of ‘Nerello mascalese’ grapes

Abstract: The effect of basal zone defoliation on vines influences yield and ripening depending on the phenological stage and its intensity. Early basal defoliation (EBD) was carried out at flowering on the autochthonous Vitis vinifera (L.) cultivar 'Nerello mascalese' grown on the eastern slopes of Mount Etna, Sicily. The effects were evaluated over a two-year period. In the first year, the canopy retained 67 % of its original leaf area after EBD and in the second year, 58 %. Compared with control vines, midday leaf wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
7
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 12 publications
(7 citation statements)
references
References 29 publications
0
7
0
Order By: Relevance
“…Many studies in recent years have focused on the effects of early defoliation and canopy management on the yield and quality aspects of grapes [30][31][32][33], and on the benefits of conservative tillage in order to reduce organic matter loss and erosion rates and increase moisture retention in the soils [2,4,34]. In previous research, we analyzed-in different climate areas and both in rainfed and irrigated vineyards-the influence of early leaf removal, identifying benefits in terms of yield traits and disease control [17][18][19][20][21][22][23][24][25][26][27]. Koblet et al [35] reported a yield decrease as a consequence of vine defoliation due to a decrease in cluster weight following a reduction in berry weight.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many studies in recent years have focused on the effects of early defoliation and canopy management on the yield and quality aspects of grapes [30][31][32][33], and on the benefits of conservative tillage in order to reduce organic matter loss and erosion rates and increase moisture retention in the soils [2,4,34]. In previous research, we analyzed-in different climate areas and both in rainfed and irrigated vineyards-the influence of early leaf removal, identifying benefits in terms of yield traits and disease control [17][18][19][20][21][22][23][24][25][26][27]. Koblet et al [35] reported a yield decrease as a consequence of vine defoliation due to a decrease in cluster weight following a reduction in berry weight.…”
Section: Discussionmentioning
confidence: 99%
“…Vine performance also depends on the agronomic practices related to the canopy control. Among these, leaf removal performed at an early stage of plant development (before bloom) represents an important tool for vine management, through a modification of the source-sink relationships [15][16][17][18][19]. In fact, a recent meta-analysis review reports that this management practice has an effect in the reduction of fruit yield and in the control of bunch rot disease.…”
Section: Introductionmentioning
confidence: 99%
“…Photosynthetically active radiation (PAR) incident on the leaf surface (Q leaf , µmol m −2 s −1 of photons) was determined simultaneously with the measurements of the eco-physiological variables, using the sensor coupled to the porometer chamber, always exposed perpendicularly to incident sunlight on the leaf surface throughout each reading. Moreover, leaf temperature (T l , • C) and CO 2 internal concentration (Ci, µmol mol −1 ) were also measured [46,47]. Following [48], the photosynthesis/transpiration ratio was taken as an estimation of instantaneous water use efficiency (WUE), and the ratio between photosynthesis/stomatal conductance, which is known as intrinsic water use efficiency, was calculated.…”
Section: Physiological Behavior and Vine Water Status Measurementsmentioning
confidence: 99%
“…These were due to the extensive olive orchards, as well as the consociations with livestock where possible [31]. For other species such as grapevines, minimum or zero tillage is commonly applied in order to regulate the vegetative and reproductive balance of vines and, in some cases, in order to reduce erosion and land degradation [32][33][34].…”
Section: Introductionmentioning
confidence: 99%